2013
DOI: 10.1103/physrevlett.111.018001
|View full text |Cite
|
Sign up to set email alerts
|

Energy Dissipation in Driven Granular Matter in the Absence of Gravity

Abstract: We experimentally investigate the energy dissipation rate in sinusoidally driven boxes which are partly filled by granular material under conditions of weightlessness. We identify two different modes of granular dynamics, depending on the amplitude of driving, A. For intense forcing, A>A(0), the material is found in the collect-and-collide regime where the center of mass of the granulate moves synchronously with the driven container, while for weak forcing, A Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
113
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(123 citation statements)
references
References 34 publications
10
113
0
Order By: Relevance
“…The collect-and-collide behavior ceases for amplitudes below a given threshold which is related to the optimal damping length. Further experiments confirm that the observed behavior holds also true for steadily driven systems [10].…”
Section: Steady State Conditionssupporting
confidence: 68%
See 1 more Smart Citation
“…The collect-and-collide behavior ceases for amplitudes below a given threshold which is related to the optimal damping length. Further experiments confirm that the observed behavior holds also true for steadily driven systems [10].…”
Section: Steady State Conditionssupporting
confidence: 68%
“…A formula to optimize granular dampers and explaining the limits of collect-and-collide is derived and validated. We also present experimental results for a steadily driven system showing that our findings are not limited to attenuated osciallators [10].…”
Section: Introductionmentioning
confidence: 95%
“…It was shown that the effective energy dissipation is carried out under the collect-and-collide regime. Additionally, Sack et al [131] performed a similar experiment with regard to steady-state systems and drew the same conclusion.The equivalent principles, based on the observation that a particle group is equivalent to a single particle, can be stated as follows:1. The void volume of the multiparticle damper is equal to that of the single-particle damper.…”
mentioning
confidence: 48%
“…When tiny particles were used (300 μm), different patterns appeared depending on the vibration frequency f, for instance, stable oscillons and surface waves similar to those observed in vibrated granular beds [15][16][17][18][19]. The above grain size dependence reveals, as in the case of granular dampers [20][21][22][23][24][25], the relevance of the main dissipation mechanism: interparticle collisions for large particles and friction as the particle size decreases.Experimental setup.-A transparent ping-pong ball (coefficient of restitution ϵ c ≈ 0.91 AE 0.02, mass m c ¼ 1.9 AE 0.1 g, and inner or outer diameter D c ¼ 3.75=3.80 AE 0.02 cm) was partially filled with liquid or grains and placed on a steel plate (mass ¼ 240 g) subjected to vertical oscillations SðtÞ ¼ A sinðωtÞ; here, A is the vibration amplitude and ω ¼ 2πf. To ensure that the ball was bouncing, we used a dimensionless acceleration Γ ¼ Aω 2 =g > 1.…”
mentioning
confidence: 92%